ANALISIS YURIDIS PERMOHONAN PAILIT PT. DUNIA TRANSPORTASI LOGISTIK TERHADAP PT. CAHAYA TIMUR GARMINDO (STUDI PUTUSAN NOMOR 2/PDT.SUS-PAILIT/2024/PN NIAGA SMG) - Mis Joni; Viola Paulina; Mazaya Aliya Jovilina (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
Background: The purpose of this research is to determine the legal consequences of applying for a bankruptcy declaration according to Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU) and to determine the judge's considerations in the case between PT. Logistics Transportation World (Creditors) to PT. Cahaya Timur Garmindo (Debtor) in Decision Number 2/Pdt.Sus-Pailit/2024/PN Niaga Smg. Research Metodes: In this research, the author uses a normative juridical approach. Findings: The research results show that the legal consequences of applying for a bankruptcy declaration according to Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU) include freezing assets, strict supervision of asset management by the curator, and distribution of assets to creditors. Conclusion: The judge's considerations in Decision Number 2/Pdt.Sus-Pailit/2024/PN Niaga Smg are based on the provisions of Article 2 paragraph (1) jo. Article 8 paragraph (4) of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, the conditions of which are (1) the Debtor has two or more creditors; (2) The debtor does not pay at least one debt that is due and collectible; (3) There are facts or circumstances that are simply proven.